Book Review: "Toward a historical Sociolinguistic Poetics of Medieval Greek", eds. A. CUOMO- E. TRAPP, Studies in Byzantine History and Civilization (SBHC 12) - ΣΚΛΑΒΕΝΙΤΗ, Αννα Σπυρίδωνος (Byzantina Symmeikta, 2018)
Book Review: Byzantios, Studies in Byzantine History and Civilization (SBHC 12) Toward a Historical Sociolinguistic Poetics of Medieval Greek, A. CUOMO- E. TRAPP (eds.) VIII+233 p., 11 b/w ill., 156 x 234 mm, 2017 ISBN: 978-2-503-57713-5 Languages: English, French, Italian.